2013
DOI: 10.1589/rika.28.573
|View full text |Cite
|
Sign up to set email alerts
|

Swing Phase Differences in Ankle Joint Angles of Young and Elderly Subjects

Abstract: The purpose of this study was to investigate the swing phase differences in ankle joint angles of young and elderly subjects. [Subjects] The subjects were 10 young persons and 14 elderly persons (no-fall group, n=10; falls group, n=4). [Method] Using a video camera we recorded the lower leg during walking and determined the maximum ankle joint angle using Dartfish software. [Results] In the young persons' group we found differences between the early and middle swing phases, and between the early and late swing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 2013, Hak et al conducted an infrared camera analysis of the margin of stability (MoS) in nine healthy young adults and reported that slow walking does not necessarily lead to walking stability and that increasing walking speed increases backward MoS and reduces the risk of falling 14 ) . A study using a video camera showed that ankle joint dorsiflexion did not change considerably during the swing phase in those who had experienced a fall 15 ) . This is because the difference between the maximum plantar flexion angle immediately after toe-off and the ankle joint angle at the end of the swing phase reduced due to a limited range of ankle joint motion or weakness of the plantar flexor muscles.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Hak et al conducted an infrared camera analysis of the margin of stability (MoS) in nine healthy young adults and reported that slow walking does not necessarily lead to walking stability and that increasing walking speed increases backward MoS and reduces the risk of falling 14 ) . A study using a video camera showed that ankle joint dorsiflexion did not change considerably during the swing phase in those who had experienced a fall 15 ) . This is because the difference between the maximum plantar flexion angle immediately after toe-off and the ankle joint angle at the end of the swing phase reduced due to a limited range of ankle joint motion or weakness of the plantar flexor muscles.…”
Section: Introductionmentioning
confidence: 99%